PENGARUH PENGGUNAAN METODE THAWING YANG BERBEDA TERHADAP KUALITAS SPERMATOZOA SEMEN SAPI PERAH BERPENGENCER TRIS SITRAT KUNING TELUR - Fachroerrozi Hoesni (Jurnal Ilmiah Universitas Batanghari Jambi, 2013)
The research was conducted in the laboratory of Department of Animal Husbandry UPTD Jambi Province, on March 23 to April 10, 2013. The purpose of this study was to determine the effect of temperature and duration of thawing and provide an overview of the effects of thawing method based on the use of different methods and duration of storage of spermatozoa temperature of dairy cows.The experimental design used was a completely randomized design (CRD) with 4 treatments and 6 replications, as treatment is longer and thawing temperatures following PI; room temperature 27 ˚ C for 60 seconds, P2; temperature of 37 ˚ C for 30 seconds, P3; temperature of 50 ˚ C for 12 seconds, P4; temperature of 70 ˚ C for 8 seconds, the observed variables that sperm motility and recovery rate of the fresh cement. Data was analyzed mengguanakan analysis of variance (ANOVA).Results of this study indicate that the thawing time and temperature affect the motility of frozen semen sap dairy (P <0,01). Each treatment on P1 thawing method: room temperature for 60 seconds, P2: temperature 37 ˚ C for 30 seconds, P3: temperature 50 ˚ C for 12 seconds and P4: a temperature of 70 ˚ C for 8 seconds. Best thawing method is the P2 treatment with optimal yield of 66.63% and is still fit for use for artificial insemination (AI).Conclusion is thawing spermatozoa method using a temperature of 37 ˚ C for 30 seconds to show the motility of frozen semen straw worth for dairy cows (IB).Keyword : use, thawing, spermatozoa